TRANSLATING NOM POETRY INTO CHINESE: EXPERIENCE AND DISCUSSION - Huyen Trang, Le Thi (VNU Journal of Foreign Studies; Vol 35 No 5DO - 10.25073/2525-2445/vnufs.4428, 2019)
Translating poetry is an interesting but challenging task. In addition to fully conveying the meaning of the original version, it is also necessary to describe the poem rhyme as well as retain the metre in the target language. Within the scope of this article, the author attempts to translate some Nom poems in the treasure of Vietnamese Nom poetry into Chinese. The translating process shows that the multi-faceted similarities between the two languages, the inheritance and development of the characteristics of Chinese Tang poetry in Nom poetry allow the translator to use the method of phonemic translation, literal translation and rhymed translation. In addition, the author gives personal perspectives on translation, as well as suggests the features which should be kept in the translation process.